Krisis Identitas Masyarakat Gili Trawangan Lombok Utara dalam Pusaran Homogenisasi Destinasi Wisata - Muhammad Azam; Ashri Ramadhan (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
This research examines the phenomenon of tourism destination homogenization in Gili Trawangan, Lombok, which is increasingly losing its local identity due to the dominance of global market logic and capitalism. Amidst the currents of 21st-century globalization, tourism tends to move toward the uniformity of architectural styles, facilities, culinary offerings, and lifestyles that disregard local cultural norms. Using a qualitative-descriptive method with a case study approach, this study aims to analyze the forms of eroding local identity and the impact of homogenization on the socio-cultural transformation of the Gili Trawangan community. The results indicate that development oriented toward short-term profit and the preferences of international tourists has led to cultural commodification, where local symbols serve merely as tourism ornaments. The dominance of foreign investors, coupled with the local community's limited capital and access to knowledge, has resulted in economic inequality and a shift in power. Lombok’s identity, known for being religious and hospitable, is slowly fading, replaced by a global entertainment culture that is inconsistent with the concept of a halal destination. Although glocalization theory offers room for adaptation, the reality on the ground shows that local people have largely become spectators of development on their own land. This research concludes the need for stricter regulations and policies that favor collective welfare to protect the cultural uniqueness of Gili Trawangan from the threat of global uniformity.